Impacto da incorporação de uma startup a partir de uma operação de corporate venture capital em uma empresa institucionalizada tradicional - Svartman, André Chevis (2024)
The challenges inherent in selecting and retaining the best talents appear as the number one adversity and concern of top business leaders today. In this dissertation, an apparent bias of this obstacle is chosen, which is the tendency for it to increase with the arrival of Generation Z, which entered the market since 2010. This was the year when the accelerated growth of emerging, innovative companies, based on disruptive technologies, began - the so-called startups. The impact of the arrival of startups on the most recent generations, including Generation Z, in professional routines and behaviors is notable. At the same time, the institutionalized organizational behavior in large corporations and more traditional companies in various sectors of the economy is still evident. This study starts from the theoretical understanding of institutions, startups, and the innovation model within such traditional companies, with a focus on open innovation, described in the work, in the injection of venture capital from corporations into startups, the corporate venture capital. The institutionalization of organizations functions similarly to myths. And often it materializes from routines and ceremoniously repeated behaviors (Meyer, J & Rowan, B; 1977). Understanding that changes in institutionalized cultures only occur through practical alterations in day-to-day routines, this work proposes, based on an ethnographic case study, to shed light on changes in routines that occurred in an institutionalized business-oriented institution (Grupo DPSP) after acquiring a startup (Ti Saúde). It was concluded that the changes that occurred brought some impacts within the traditional company's way of working during two diferente periods. An initial period from when the startup was acquired until its two years within the company's ecosystem, during which little changed due to a less than ideal integration of Ti Saúde. And a second period, still ongoing, when the company begins to perceive the ongoing institutional changes and the challenges that such changes bring